Fusion assays for screening of fusion inhibitors targeting SARS-CoV-2 entry and syncytia formation - Chan, Shiu-Wan (Frontiers in Pharmacology, 2022)
Virus fusion process is evolutionarily conserved and provides a promising pan-viral target. Cell-cell fusion leads to syncytial formation and has implications in pathogenesis, virus spread and immune evasion. Drugs that target these processes can be developed into anti-virals. Here, we have developed sensitive, rapid, adaptable fusion reporter gene assays as models for plasma membrane and alternative fusion pathways as well as syncytial fusion in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and have confirmed their specificity using neutralizing antibodies and specific protease inhibitors. The fusion report gene assays are more sensitive and unbiased than morphological fusion assay. The fusion assays can differentiate between transmembrane serine protease 2 (TMPRSS2)-dependency in TMPRSS2(+) cells and trypsin-dependency in angiotensin-converting enzyme 2 (ACE2)(+)TMPRSS2(-) cells. Moreover, we have identified putative novel fusion processes that are triggered by an acidic pH with and without trypsin. Coupled with morphological fusion criteria, we have found that syncytia formation is enhanced by TMPRSS2 or trypsin. By testing against our top drug hits previously shown to inhibit SARS-CoV-2 pseudovirus infection, we have identified several fusion inhibitors including structurally related lopsided kite-shaped molecules. Our results have important implications in the development of universal blockers and synergistic therapeutics and the small molecule inhibitors can provide important tools in elucidating the fusion process.